Unfree and Unequal: A Butlerian Postulation of the Violence of Homelessness - Eloff, Zahlé (The Stellenbosch Socratic Journal, 2023)
In The Force of Nonviolence (2020), Judith Butler introduces the notions of “violence”, “nonviolence”, “grievability”, and “vulnerability”. In this paper, Butler’s four notions will be applied to explain how homelessness is a kind of violence that renders certain lives more grievable than others. Unequal grievability means that if the life of a homeless person were to be lost, it would not be recognised as a loss at all. Jeremy Waldron’s Homelessness and the Issue of Freedom (1991) is instrumental in illustrating the ungrievability of homeless persons by focusing on his distinction between private and collective property. Addressing this violence of homelessness requires nonviolent action such as banning anti-homeless architecture and working within institutional structures to create a radically egalitarian grievable environment.